Performance reviews : evaluate performance, offer constructive feedback, discuss tough topics - Cabus, Mark (20 minute manager series., 2022)
Conducting performance reviews can be stressful. But these conversations are critical to your employees' development, allowing you to formally communicate with them about their accomplishments relative to their goals. Performance Reviews guides you through the basics. You'll learn to: - Gather and analyze the right information - Document your assessment - Address performance problems - Set challenging goals Don't have much time? Get up to speed fast on the most essential business skills with HBR's 20-Minute Manager series. Whether you need a crash course or a brief refresher, each book in the series is a concise, practical primer that will help you brush up on a key management topic. Advice you can quickly listen to and apply, for ambitious professionals and aspiring executives-from the most trusted source in business.